2017
DOI: 10.1111/jace.14774
|View full text |Cite
|
Sign up to set email alerts
|

Fiber‐draw‐induced elongation and break‐up of particles inside the core of a silica‐based optical fiber

Abstract: Particles in the core of optical fibers are widely studied to tailor or to improve optical properties. The analysis of nanoparticles embedded in silica‐based optical fiber allowed new observations of the evolution of amorphous particles during fiber drawing. Even at the nanoscale, competition between viscous stresses and surface tension on the particles induces elongation and even break‐up of particles during the process. Indeed, particles between 140 and 200 nm diameter inside the preform can break up in frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 24 publications
2
17
0
2
Order By: Relevance
“…Indeed, "dumb-bell" shaped nanoparticles (particles elongated between two rounded ends, as already reported in Ref. 7) and break-up were observed only in Mg2 fiber where, in fiber Mg1, all of the elongated particles ends with well-defined points. For the dumb-bell shaped particles, both rounded ends can be slightly different because the surface of the polished sample is not perfectly parallel to the large axis of these particles.…”
Section: Influence Of the Compositionsupporting
confidence: 76%
See 1 more Smart Citation
“…Indeed, "dumb-bell" shaped nanoparticles (particles elongated between two rounded ends, as already reported in Ref. 7) and break-up were observed only in Mg2 fiber where, in fiber Mg1, all of the elongated particles ends with well-defined points. For the dumb-bell shaped particles, both rounded ends can be slightly different because the surface of the polished sample is not perfectly parallel to the large axis of these particles.…”
Section: Influence Of the Compositionsupporting
confidence: 76%
“…However, thermodynamic and rheological effects are known to modify the shape and structure of the particles during fiber formation. Indeed, the Authors have recently reported the evolution of nanoparticles during the fiber draw process and showed that fiber drawing itself can induce particle elongation and break-up through rheological mechanisms, triggered by Rayleigh-Plateau capillary instabilities [7]. In this article, we discuss in more detail the parameters (composition and the drawing temperature) that allow for greater tailorability of the nanoparticle morphology in the fibers.…”
Section: Introductionmentioning
confidence: 93%
“…Magnesium-rich particles in the SEM image on the right appear less clear than the lanthanum-rich particles (on the left) because the chemical contrast between magnesium and silica is lower than that between lanthanum and silica. The origin of the elongated particles in both images is discussed in previous papers [16,17]. Figure 2 shows the increase in the La content along the length of the optical fiber, which is in agreement with the increasing soaking time with the second doping solution.…”
Section: Methodssupporting
confidence: 81%
“…However, from the geometrical considerations, it is clear that their shape should evolve. Recently, to shed more light on this question, Vermillac et al studied the morphologies of oxide particles in optical fibers [191,192]. It was found that during the drawing step, the spherical particles present in the preform could be elongated and even broken up into smaller particles (Figure 6b).…”
Section: Phase-separated Fibersmentioning
confidence: 99%